Photoinduced metal-free diboration of alkynes in the presence of organophosphine catalysts. Issue 48 (1st December 2016) - Yoshimura, Aya; Takamachi, Yuki; Mihara, Kei; Saeki, Tomokazu; Kawaguchi, Shin-ichi; Han, Li-Biao; Nomoto, Akihiro; Ogawa, Akiya
Abstract: In sharp contrast to the transition metal-catalyzed diboration of alkynes with diboron species such as B2 pin2, which affords vicinal cis -diborated alkenes, the organophosphine-catalyzed addition of B2 pin2 to alkynes proceeds under metal-free conditions upon photoirradiation to give the corresponding vicinal trans -diborated alkenes with good stereoselectivity. For example, the photoinduced diboration of 1-octyne with B2 pin2 in the presence of tris( o -methylphenyl)phosphine afforded 1, 2-diborated octene with excellent trans selectivity ( trans / cis =95/5). The influence of various organophosphines on the diboration is described in detail. The diboration does not occur in the dark or in the absence of an organophosphine catalyst. Moreover, ESR (electron spin resonance) measurements of the reaction mixture revealed a radical species around g =2.003, supporting a radical pathway for the organophosphine-catalyzed diboration. In addition, the photoinduced cis to trans isomerization of vicinal cis -diborated alkenes in the presence/absence of organophosphines is discussed. Graphical abstract: